Emodin Attenuates Cigarette Smoke Induced Lung Injury in a Mouse Model via Suppression of Reactive Oxygen Species Production. Issue 11 (2nd July 2015) - Xue, Wen‐hua; Shi, Xiu‐qin; Liang, Shu‐hong; Zhou, Lin; Liu, Ke‐feng; Zhao, Jie
ABSTRACT: Emodin has antioxidative activities. Here, we investigated the effects of emodin on cigarette smoke (CS)‐induced acute lung inflammation. Mice (C57BL/6) were exposed to CS. Emodin was administrated with intraperitoneal bolus injection of emodin (20 or 40 mg/kg) daily 1 h before CS exposure. Emodin inhibited CS‐induced inflammatory cells infiltration in mouse lungs, especially at 40 mg/kg. Moreover, emodin resulted in significant reductions in total bronchoalveolar lavage fluid (BALF) cells, as compared with air exposure control, coupled with decreases in BALF cytokines. The activities of superoxide dismutase, catalase, and glutathione peroxidase were remarkably enhanced by emodin in CS‐exposed mice. Emodin enhanced CS‐induced expression of heme oxygenase‐1 and nuclear factor‐erythroid 2‐related factor‐2 (both are antioxidative genes) at both mRNA and protein levels, and profoundly promoted their activities in CS‐treated mice. Collectively, our results suggested that emodin protects mouse lung from CS‐induced lung inflammation and oxidative damage, most likely through its antioxidant activity.